2020
DOI: 10.3389/fendo.2020.556610
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Medicine: Lessons Learned From Monogenic and Complex Bone Disorders

Abstract: Current genetic studies of monogenic and complex bone diseases have broadened our understanding of disease pathophysiology, highlighting the need for medical interventions and treatments tailored to the characteristics of patients. As genomic research progresses, novel insights into the molecular mechanisms are starting to provide support to clinical decision-making; now offering ample opportunities for disease screening, diagnosis, prognosis and treatment. Drug targets holding mechanisms with genetic support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 199 publications
0
5
0
Order By: Relevance
“…Family history of hip fractures . It has been suggested that the degree of bone remodeling and geometry may depend on genetic factors [ 44 ]. The occurrence of hip fractures in the immediate family is included among the clinical factors in the FRAX form [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…Family history of hip fractures . It has been suggested that the degree of bone remodeling and geometry may depend on genetic factors [ 44 ]. The occurrence of hip fractures in the immediate family is included among the clinical factors in the FRAX form [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to [22], the degree of bone remodeling may depend on genetic factors. It is estimated that genetic factors influence the occurrence of low-energy fractures in 25-35%.…”
Section: History Of Hip Fractures In Parents (Fam/hip)mentioning
confidence: 99%
“…It might also reflect the idea that clinical variability, observed in many monogenic diseases, can be explained by variants in modifier genes ( 19 ). The discovery of such genetic variants opens an application window into personalized medicine ( 20 ).…”
Section: Causality Of Genetic Mutations Associated With Rare Skeletal Diseases Requires Proofmentioning
confidence: 99%